A Comparative Analysis of In-Cylinder Flow, Heat Transfer and Turbulence Characteristics in Different Type Combustion Chamber - Fırat, Müjdat; Varol, Yasin (My University, 2018)
Recently some studies have been carried out on combustion chamber design for diesel and gasoline engines; however, they routinely used piston bowl model approach, which may neglect interactions with cylinder head design. Fluid motion within the cylinder of internal combustion engines has a significantly influence on the combustion process and engine efficiency. The aim of this study two different geometries of the combustion chamber of internal combustion engine were compared in terms of in cylinder flow and heat transfer during the intake process. For this, complete calculations of the intake stroke were performed under realistic operating conditions and heat transfer, velocity and turbulence flow fields obtained in each combustion chamber investigation detail. They were solved with finite volume method and ANSYS-Fluent 12.0 commercial code. The findings include using k-? turbulence model and dynamic mesh generation model for different crank angle. The result of studies show that flow structure and turbulence intensity are affected on combustion chamber geometries. Also, the pent-roof type combustion chamber configuration was found to generate turbulence intensity more efficiently than the conventional type combustion chamber.
Keywords: Fizik; Uygulamalı; Mühendislik; Makine; Termodinamik